Protection for minor invention: an analysis of the Malaysian model / Norsyazwani Che Aziz ...[et al.] - Che Aziz, Norsyazwani; Roslan, Nurul Nazmin; Ali, Farah Syazwana; Sy Mohamad, Sharifah Fatiha (2010)
The importance of utility innovation in Malaysia is to give protection for the applicant who is unable to obtain a protection for standard patent. The majority of applications for utility innovation come from foreign applicants compared to the applications from Malaysian applicants. As compared to standard patent the application for utility innovation is low and dropping. Thus, there is a need to analyze the provision of the law relating to utility innovation to determine how it can be improved to encourage wider usage of the utility innovation protection. "Protection for Minor Invention: An Analysis of the Malaysian Model" is the title of this project paper. There are three main objectives to this study which are to analyze the provision of the law relating to utility innovation in Malaysia, innovation patent in Australia and utility model in Japan and Germany and to study the weaknesses of our utility innovation system and to suggest reforms for improvements. This research focuses on the law on utility model in Malaysia and other countries such as Germany, Australia and Japan and the differences in each utility model system and law of those countries. The qualitative type of research techniques and a library based research were used in carrying out this research.